Assessing physical behavior through accelerometry – State of the science, best practices and future directions. (July 2020) - Burchartz, Alexander; Anedda, Bastian; Auerswald, Tina; Giurgiu, Marco; Hill, Holger; Ketelhut, Sascha; Kolb, Simon; Mall, Christoph; Manz, Kristin; Nigg, Claudio R.; Reichert, Markus; Sprengeler, Ole; et al.
Highlights: Use 24h objective recording of physical activity in real life over a period of several days and weeks. Accelerometers can easily be used in various applications like interventions, epidemiology and surveillance. Consider existing validation studies when planning one's own studies and document as many technical decisions as possible. Assess the type of activity performed during non-wear time and reasons for non-wear of the devices. Accelerometers can collect even more data to evaluate with current sensors developments.